2014
DOI: 10.4253/wjge.v6.i4.137
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of SpyGlassTM-directed biopsy compared to brush cytology in obtaining adequate tissue for diagnosis in patients with biliary strictures

Abstract: SpyGlass(TM) imaging can be recommended for proper inflammatory diagnosis in PSC patients. However, its value in diagnosing dysplasia was not addressed in this study and requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…The diagnostic yield of TB under SOCS in the current study was comparable to that reported by previous studies [11][12][13][14][15][16][17][18][19]. Many of the previous reports noted that more than three tissue samples were required for an accurate diagnosis, as the relatively small tissue samples obtained by SpyBite  rendered pathological examination challenging.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The diagnostic yield of TB under SOCS in the current study was comparable to that reported by previous studies [11][12][13][14][15][16][17][18][19]. Many of the previous reports noted that more than three tissue samples were required for an accurate diagnosis, as the relatively small tissue samples obtained by SpyBite  rendered pathological examination challenging.…”
Section: Discussionsupporting
confidence: 78%
“…The SpyGlass  system by Boston Scientific is a recently launched single-operator cholangioscopy (SOCS) [10]. The sensitivity, specificity, and accuracy of targeted biopsy (TB) of biliary strictures using SpyGlass  were reported as 49-88%, 82-100%, and 25-88%, respectively [11][12][13][14][15][16][17][18][19]. However, a meta-analysis showed that the sensitivity of the SpyGlass  system was only moderate; thus, its diagnostic value requires improvement [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnosis obtained via SOCP in our study was subject to error, which is consistent with previously published findings (6,14,47). While there are no validated criteria available that enable the differentiation between malignant and benign endoscopic lesions in vivo, we used criteria defined in previous studies to perform an endoscopic diagnosis (6,27,35,36). There was a sensitivity and specificity of 88% and 80%, respectively, in our study, which are similar to those of recently published studies (84.5-95% and 79-92.6%, respectively) (6,22,31).…”
Section: A B C Dsupporting
confidence: 86%
“…A single comparative study of SpyGlassdirected biopsy and brush cytology demonstrated little incremental yield for diagnosis of dysplasia or malignancy. 115 No other comparative data are available for the analog or digital iterations of the single-operator SpyGlass system.…”
Section: Cholangioscopy For Bile Duct Stricturesmentioning
confidence: 99%